(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2022)
This article discusses university dance education through artistic-pedagogical approaches according to notions of ancestry and spirituality from Afro-Amerindian cultures, based on three teaching experiences in higher education. The combination of curricular structure, pedagogical and artistic projects, in line with the students’ life stories, collaborates with the opening of fissures in the monoculture of knowledge established at the university. The recognition and production of Afro-Amerindian poetics is materialized through creative and pedagogical processes in experiences with traditional cultural practices, which reflect (re)existence performances based on insurgent corporeality and narratives.